Tourism Social Entrepreneurship Pedagogy as an Approach for the Development of Family Business Enterprise Competencies (Eurasian Journal of Learning and Academic Teaching, 2022)
The study explores tourism social entrepreneurship pedagogy as an approach for the development of family business enterprise competencies. Tourism scholars and educators are challenging the long-standing assumption that education should meet the needs of industry and have begun asking what can be done to help tourism students think more broadly and critically about the tourism social entrepreneurship. The paper moved ‘beyond’ the classroom to assess tourism's broader role as (critical) pedagogy in the application of competency skills for innovative development. One of the aim of the study is to examine the possibility of using pedagogy approach to develop a family business enterprise competencies that will change the status quo of social injustices, tackle some of humanity's greatest social problems, and launch businesses to create markets that advance the common good of the local populace. The study adopted the descriptive-survey design method where a sample of one hundred and fifteen respondents were administered with a questionnaire and data was obtained and use to test the hypotheses based on t-test using SPSS version 21. Results from the findings revealed that provision of training and development is the major pedagogical approach leading to higher and better competency skills in social entrepreneurship. This relationship was found statistically significant at P < 0.05. This implied that the receiving tourism social entrepreneurship training increases the score of quality job performance of entrepreneurs where pedagogy approach is applied. The study concludes that pedagogy approach to tourism social entrepreneurship will serve as a good strategy for family business competency skill development that could yield to greater innovation in tourism entrepreneurship technology and related business enterprises. The study however, recommends that the pedagogy approach should be incorporated into the hospitality and tourism entrepreneurship curriculum to serve as a holistic approach to teaching and learning among final year students